2017
DOI: 10.1515/ijfe-2016-0309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vacuum Impregnation on Drying Kinetics and Selected Quality Factors of Apple Cubes

Abstract: The possibility of using the vacuum impregnation as a pretreatment before drying apple cubes was investigated. The impregnation was carried out for 4.5 min with the vacuum pressure of 0.01 MPa. The sucrose solution or a mixture of sucrose and the citric acid were used as infiltration liquids. Apple cubes were dried by convective drying (CD) (at temperature of 50 and 70 °C) or microwave-vacuum drying (MVD) (at power of microwaves 120 and 480 W). The drying kinetics was determined and quality factors (anti-oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This phenomenon can also be observed when analyzing the changes of the constants in the Page Model: the parameter k rose with increasing temperature (from 1.1400 to 1.1576) and the constant n increased slightly (from 0.0130 to 0.0137) ( Table 1). A similar correlation between microwave power and the process time was observed in studies involving the MFB drying of apples 29 and soya. 30 MV drying was the fastest of all the tested methods for lemon thyme dehydration.…”
Section: Drying Kineticssupporting
confidence: 74%
“…This phenomenon can also be observed when analyzing the changes of the constants in the Page Model: the parameter k rose with increasing temperature (from 1.1400 to 1.1576) and the constant n increased slightly (from 0.0130 to 0.0137) ( Table 1). A similar correlation between microwave power and the process time was observed in studies involving the MFB drying of apples 29 and soya. 30 MV drying was the fastest of all the tested methods for lemon thyme dehydration.…”
Section: Drying Kineticssupporting
confidence: 74%
“…The lowest value was observed in OD samples while the highest value was observed in ST samples. Pasławska et al [2017] and Kowalska et al [2018] reported similar phenomenon of TA value decrease after fruit immersion in a sugar solution. The changes in TA may be attributed to the elution of organic acids from tissue during OD process [Kowalska et al, 2018].…”
Section: Chemical Characterizationmentioning
confidence: 56%
“…The loss in V C was attributed to the thermal disruption and leakage of water-soluble V C during pretreatment [Wang et al, 2018;Horuz et al, 2017]. However, it was reported that the presence of sugar would stabilize vitamin C in fruits [Pasławska et al, 2017].…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of reduced pressure, the material comes into contact with the impregnating liquid, and then atmospheric pressure is restored, while a solution of various components penetrates the material’s porous surface until a balanced pressure is achieved (impregnation stage) [ 22 ]. There is a large amount of literature focused on effects of VI conditions on mass transfer phenomena or structure and mechanical properties of impregnated material [ 20 , 21 , 22 , 23 , 24 , 25 ]. However, little is known about the chemical modifications induced by pressure changes and/or impregnated molecules influencing nutritional properties of processed vegetables.…”
Section: Introductionmentioning
confidence: 99%